Vaccinium dwarf shrubs responses to experimental warming and herbivory resistance treatment are species- and context dependent - Hegland, Stein Joar; Gillespie, Mark A. K. (Frontiers in Ecology and Evolution, 2024)
Climate change impacts on species and ecosystem functioning may depend on climatic context and study systems. Climate warming and intensified herbivory are two stressors to plants that often appear in combination and are predicted to increase in cold environments. Effects of multiple drivers on plant performance are difficult to predict and warrant studies that use experimental manipulations along climatic gradients to produce more realistic knowledge. Our three study sites by the Sognefjord in Norway, that differed mainly in climatic conditions (ca. 5°C growing season difference), ranged from hemi-boreal lowland (100 masl, Low), via boreal mid-montane (500 masl) to alpine timberline (900 masl, High) bioclimates. At each site, in a randomized block design, we simulated growing-season warming using open-top chambers (OTCs) and experimentally induced herbivory resistance using the plant hormone methyl jasmonate (MeJA). We recorded growth, mortality, flower and fruit numbers, and insect herbivory on tagged ramets in permanent plots across three years (2016-2018) in three open woodland populations of two functionally important plant species with contrasting traits, Vaccinium myrtillus (bilberry) and V. vitis-idaea (lingonberry). Growth of both dwarf shrubs decreased with warming in the warm lowland populations (Low) but increased in the alpine populations (High). Shoot mortality increased most with warming at Low but was reduced at High. Reproduction, both flowering and fruiting, decreased with induced resistance treatment, but the effect was larger when warmed for bilberry and increased with elevation for both species. Leaf herbivory in bilberry increased with warming at Low but decreased at High. The combined warming and resistance treatment had only synergistic negative interaction effects on fruit numbers in bilberry. The clear context- and species-dependent effects of climate warming and increased resistance in this study may predict a potential decline in performance, as well as abundance and distribution, of these functionally important Vaccinium species at our lowest site. Bilberry reproduction appeared to be particularly susceptible to both climate warming and induced resistance in the manipulated populations. Such combined negative effects on plant performance are likely to have considerable knock-on effects via altered species’ interactions and ecosystem functioning.